2023
DOI: 10.1007/s11356-023-27901-6
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the management of food waste in developing countries: with special reference to India

Abstract: Up to one third of the food that is purposely grown for human sustenance is wasted and never consumed, with adverse consequences for the environment and socio-economic aspects. In India, managing food waste is a significant environmental concern. Food waste output is increasing in Indian cities and towns as a result of the country’s urban expansion, modernization, and population growth. Poor management of food waste can have negative consequences for the environment and pose a risk to the public’s health issue… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 183 publications
0
2
0
Order By: Relevance
“…This process can be challenging due to the diverse sources of food waste, ranging from crop processing to household leftovers. 111 Efficient collection systems need to be in place to gather sufficient quantities of waste materials that can be used in material production processing. Then, once the waste has been collected, the waste must be separated into its various components.…”
Section: The Use Of Agro-waste and Its Challenges For Sustainable Foo...mentioning
confidence: 99%
“…This process can be challenging due to the diverse sources of food waste, ranging from crop processing to household leftovers. 111 Efficient collection systems need to be in place to gather sufficient quantities of waste materials that can be used in material production processing. Then, once the waste has been collected, the waste must be separated into its various components.…”
Section: The Use Of Agro-waste and Its Challenges For Sustainable Foo...mentioning
confidence: 99%
“…The most common food waste treatment method in India is dumping/landfills (including illegal dumps and landfills) accounts for over 90% of food waste treatments. 97 Comparing anaerobic digestion, landfill, incineration, composting and heat-moisture treatments showed that landfill contributes most to climate change and is about 10 times larger than the other food waste management methods. 98 Existing and emerging solutions to reduce (packaging, distribution, inventory management, temperature control, increased produce shelf life, consumer campaigns and education, suboptimal food use, food sharing, and portion control), recover (donations, imperfect food redistribution, surplus food recovery networks, and upcycling/remanufacturing) and recycle (animal feed, anaerobic digestion, composting, incineration, disposal, biorefining, and biofuel production) food loss and waste have been summarized previously.…”
Section: Food Waste Generation and Re-usementioning
confidence: 99%
“…These differences can be mapped within the framework and integrated within it. The patterns may also change over time due to a crisis like COVID-19 [38], type of use [39], the socioeconomic development of society [40,41], and other factors. These changes too can be integrated within the framework.…”
Section: Differentiation and Integration Of Flwmentioning
confidence: 99%